Características da carne de cordeiros alimentados com glicerina proveniente da produção de biodiesel - Borghi, Thiago Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This trial aimed to evaluate the physicochemical, sensory and nutritional characteristics of different muscles from lambs fed diets without and with glycerin inclusions, replacing corn. Thirty Ile de France non-castrated lambs with 45 days of age and about 15 ± 0,2 kg of body weight were confined in individual pens and slaughtered at 32 ± 0,2 kg. The treatments consisted of three diets: D0 - sugar cane + concentrate; D10 - sugar cane + concentrate + 10% glycerin and D20 - sugar cane + concentrate + 20% glycerin; and three muscles: Triceps brachii, Semimembranosus and Longissimus lumborum. No interactions were observed (P>0.05) between treatments and types of muscle in all the evaluated quality characteristics. The muscles of the lambs are similar in terms of physical-chemical, sensory and nutritional characteristics, so that only differ (P<0.05) in sarcomere length, diameter of muscle fibers and cholesterol content. The inclusion of glycerin in the diets of the lambs did not affect (P>0.05) the physicochemical characteristics pH, temperature, water holding capacity (24 hours and 30 days after slaughter), weight loss by thawing and cooking, strength shear, diameter of muscle fibers, sarcomere length, lipid oxidation, sensory attributes, chemical composition and meat cholesterol content. There were linear effect (P<0.05) with decrease on the variable b * (yellow intensity) of the muscles (3.79 to 3.09) and subcutaneous fat (8.20 to 7.02). In the fatty acid profile of the intramuscular fat, there were effects (P<0.05) of the glycerin inclusions, with increase in the concentration of heptadecanoic acid (1.64 to 2.61%) and sum of the fatty acids of the omega-family 3 (0.10 to 0.18%) and decrease in omega-6:omega-3 ratio (33.70 to 19.63). The inclusion of glycerin in the diet, replacing corn, did not affect the quality characteristics of the meat, confirming the possibility of using this co-product of the production of Biodiesel in ...

O objetivo deste trabalho foi avaliar as características físico-químicas, sensoriais e nutricionais de diferentes músculos de cordeiros Ile de France terminados em confinamento, recebendo dietas sem e com inclusões de glicerina, em substituição ao milho. Foram utilizados 30 cordeiros machos não castrados com aproximadamente 45 dias de idade e 15 ± 0,2 kg de peso corporal, alojados em baias individuais e abatidos aos 32,0 ± 0,2 kg. Os tratamentos foram compostos por três dietas: D0 - cana-de-açúcar + concentrado; D10 - cana-de-açúcar + concentrado + 10% de glicerina e D20 - cana-de-açúcar + concentrado + 20% de glicerina; e três músculos: Triceps brachii, Semimembranosus e Longissimus lumborum. Não foi observada interação (P>0,05) entre as dietas e os tipos de músculo em todas as características qualitativas avaliadas. Os músculos dos cordeiros são semelhantes quanto às características físico-químicas, sensoriais e nutricionais, tanto que só diferiram (P<0,05) no comprimento de sarcômero, diâmetro das fibras musculares e teor de colesterol. A inclusão de glicerina na dieta dos cordeiros não afetou (P>0,05) as características físico-químicas pH, temperatura, capacidade de retenção de água (24h e 30 dias após o abate), perdas de peso por descongelamento e cocção, força de cisalhamento, diâmetro das fibras musculares, comprimento de sarcômero, oxidação lipídica, os atributos sensoriais, a composição centesimal e o teor de colesterol da carne. Houve efeito linear (P<0,05) decrescente para as variáveis b* (intensidade de amarelo) nos músculos (3,79 para 3,09) e na gordura subcutânea (8,20 para 7,02). No perfil de ácidos graxos da gordura intramuscular, houve efeito (P<0,05) da inclusão de glicerina, com elevações na concentração do ácido heptadecanoico (1,64 para 2,61%) e no somatório dos ácidos ...
Keywords: Cordeiro; Carne ovina; Acidos graxos; Acidos graxos Omega-3; Musculos; Lambs